The Relationship between Mental Workload and Job Satisfaction of Faculty Members with their Educational Performance - Neda Mahdavi; Masoud Shafiee Motlagh2; Zahra Cheraghi; Hossein Jafari Mansoorian; Vajihe Ramazani Doroh; Leili tapak; Maryam Afshari; Amin Doosti-Irani (Journal of Medical Education and Development)
Introduction: Workload and job satisfaction are among the most influential factors affecting job performance. Therefore, this study aims to assess the cognitive workload and job satisfaction and their impact on the quality of education faculty members provide. Method: This study was conducted among 34 faculty members through a census. The NASA-TLX tool was used to assess cognitive workload, and a job satisfaction scale was employed to evaluate job satisfaction. Moreover, the training quality score was considered a criterion for assessing the educational performance of the participants. To determine the role of explanatory variables on the level of mental workload, multiple linear regression was used at a 95% confidence level. Result: The mean cognitive workload of faculty members was 52.94 ± 24.48. Efficiency and time demand scored the highest and lowest among the subscales of workload, respectively. Job satisfaction was 56.85 ± 27.61, with satisfaction with the department head and colleagues ranking highest and satisfaction with salary being the lowest in job satisfaction. The cognitive workload had a non-significant relationship with job satisfaction (P = 0.08, r = 0.56). However, the relationship between teaching quality and both cognitive workload and job satisfaction was not statistically significant. Conclusion: No significant relationship was observed between cognitive workload, job satisfaction, and teaching quality scores. However, it is recommended that measures be taken to improve the quality of work life for faculty members to enhance the quality of education they provide.